2019
DOI: 10.1038/s41467-019-13098-1
|View full text |Cite
|
Sign up to set email alerts
|

Geminal group-directed olefinic C-H functionalization via four- to eight-membered exo-metallocycles

Abstract: Great efforts have been made in the activation of a C(alkenyl)-H bond vicinal to the directing group to proceed via five- or six-membered endo-metallocycles. In stark contrast, functionalization of a C(alkenyl)-H bond geminal to the directing group via exo-metallocycle pathway continued to be elusive. Here we report the selective transformation of an olefinic C-H bond that is geminal to the directing group bearing valuable hydroxyl, carbamate or amide into a C-C bond, which proceeds through four- to eight-memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…Zhong and coworkers reported the palladium‐catalyzed activation of C(alkenyl)−H bond geminal to the directing group (hydroxy, carbamate and amide) through formation of rare exo ‐metallacycle intermediate ( Scheme 16). [64] Although ( Z )‐allyl alcohol 35 provided alkenylation products 37 in low yield, the strategy afforded high product yields from homologous alcohols owing to the formation of unstrained five‐ or six‐membered metallacycle.…”
Section: C−h Activation Using Palladiummentioning
confidence: 99%
“…Zhong and coworkers reported the palladium‐catalyzed activation of C(alkenyl)−H bond geminal to the directing group (hydroxy, carbamate and amide) through formation of rare exo ‐metallacycle intermediate ( Scheme 16). [64] Although ( Z )‐allyl alcohol 35 provided alkenylation products 37 in low yield, the strategy afforded high product yields from homologous alcohols owing to the formation of unstrained five‐ or six‐membered metallacycle.…”
Section: C−h Activation Using Palladiummentioning
confidence: 99%
“…The salient feature of Pd catalysis with the phenanthroline bidentate auxiliary is that the scope of allylic alcohols was broader than that of reported procedures. ,, The reaction was compatible with the 4,4-dimethylcyclohexenol 1b as well as larger seven-membered and smaller five-membered allylic alcohols 1c and 1d ( 3ba – da ). The structure of 3ba was unambiguously confirmed by X-ray crystallography (CCDC 1990132).…”
mentioning
confidence: 95%
“…Engle also developed the 8-aminoquinoline-directed, Pd-catalyzed regioselective C–H alkenylation but with just two examples of allylic alcohols . Very recently, Zhang and Zhong disclosed the more general C–H alkenylation strategy by using the carbamate directing group . However, all reported procedures are still restricted in scope: only terminal or cis -allylic alcohols could be employed.…”
mentioning
confidence: 99%
“…To date, most of the alkenyl C–H activation was carried out by a five- or six-membered metallacycle pathway; a further size enlargement will make the bonds more rotatable, thus reducing the stability. Besides, the propensity for exo -metallacycle formation can be increased by either eliminating the potential formation sites of endo -metallocycle or incorporating a suitable coordinating entity to promote chelation (formation of an extra 5- or 6-membered exo -metallocycle will restrain the endo -metallocycle and increase exo -metallocycle structural rigidity) . As far as we are concerned, only a few reports with exo -metallocycle mechanisms have been revealed. Dong and others revealed outstanding strategies by using oxime as the exo -directing groups for the selective C­(sp 3 )–H acetoxylation, intramolecular alkoxylation, amidation, and fluorination via a five-membered exo -palladacycle . Engle’s group reported a C­(sp 2 )–H functionalization via a palladium-involved six-membered exo -palladacycle directed by N,N -bidentate auxiliary which was then removed by a nickel-catalyzed methanolysis to provide the corresponding ester .…”
mentioning
confidence: 99%
“…Carreira et al demonstrated the palladium-catalyzed C–H iodination and alkynylation of unactivated olefins by picolinamide as the directing group . Zhong et al have achieved alkenyl C–H bond functionalization of amides, carbamates, and alkenyl alcohols through weakly O -monodentate coordination (Scheme b) …”
mentioning
confidence: 99%